Size-dependent retention of elongate mineral particles in human lungs: modeling and implications for risk assessment - Korchevskiy, Andrey; Attanoos, Richard; Wylie, Ann G. (Frontiers in Public Health, 2025)
IntroductionLung deposition of elongate amphibole particles is an important process impacting the risk of cancer. There is, however, a significant gap in scientific literature characterizing the role of particle size in the differences observed for deposition and clearance rate in the human respiratory system. The purpose of the paper is to explore the relationship between size distribution of elongate mineral particles in human lungs compared to corresponding distribution in the airborne exposure.Materials and methodsPreviously published information about lung deposition for amosite and crocidolite particles in various dimensional groups, collected by the team of Pooley and Clark was reanalyzed with application of recently developed methodologies for fiber size analysis. The new metric—deposition selection ratio (DSR) is proposed; it is found by dividing the size fraction of particles in lungs to the corresponding fraction in exposure. The DSR estimations were also compared to theoretical estimations of pulmonary deposition rates of particles based on the United States Environmental Protection Agency (US EPA) Multi-Path Particle Dosimetry (MPPD) model.ResultsIt was demonstrated that DSR values can be approximated by using log–log regressions with length and width of particles as independent variables. For non-asbestiform particles (cleavage fragments), the prediction of DSR from parametric and non-parametric models is demonstrated to be less than 1 (evidence of deselection in lungs). Negative correlation was found for DSR estimations and the theoretical predictions of pulmonary deposition rates by MPPD.DiscussionThe observed data for size-specific lung deposition of elongate mineral particles can be used for quantitative estimates of risk and analysis of toxicokinetic processes in human lungs. The difference between theoretical model and observed fiber deposition pattern requires further adjustments in the methods to predict lung deposition of elongate particles.